The Best of Soccer Journal - Techniques and Tactics (Meyer & Meyer Sport (UK) Ltd., 2012)
"The Best of Soccer Journal - Technique and Tactics" offers an in depth look at teaching techniques, skills and tactics for the soccer coach. The material is suitable for coaching all ages of soccer players. The articles were originally published in Soccer Journal between 1990 and 2010. - Klappentext -